Correlations between trust and the organizational citizenship behaviors: reflections and considerations for public managers from a municipality in Minas Gerais - Silva, Wagner Ferraz Coelho da; Paiva, Wanderléia da Consolação; Silva, Helder Antônio da (Revista de Administração da UFSM, 2019)
This quantitative approach study aimed to investigate the influence of dimensions of trust over expressions of organizational citizenship behaviors (OCBs) in the total sample of civil servants from two public management units in a city in Minas Gerais. Data collection was held by applying a sociodemographic survey, the Behavioral Trust Inventory (BTI), the Public Relations Relationship Measurement Scale (PR-RMS) and the Behavioral Intentions of Organizational Citizenship Scale (EICCOrg) in a sample of 81 civil servants. Data was treated using the Statistical Package for Social Sciences – SPSS version 22. Results confirmed the existence of a positive relation between the dimensions of trust and OCB both for the total sample and for the subsamples. The existence of peculiarities conditioning both the correlations and the explanatory power of trust variables was found in the total sample and subsamples of Health and Education sectors. This work expects to contribute to public managers so that they can develop actions that enhance the levels of trust and promote more cooperative environments with OCBs manifestations, favoring, therefore, the organizational climate and guaranteeing the services’ users are satisfied.